Structural dynamics and in silico design of pyrazolopyran-based inhibitors against Plasmodium serine hydroxymethyltransferases - Mee-udorn P. (2023)
The clinical efficacy of antimalarial drugs has been reduced due to resistance spreading over many parts of the world. Target-based approaches on attractive drug targets, such as Plasmodium serine hydroxymethyltransferases (SHMTs) exhibiting distinct structure and function as well as kinetic mechanisms from the human enzyme homologue, are highly useful methods to be used for bypassing the present resistance in the field. Herein, 500-ns molecular dynamics (MD) simulations were carried out to investigate the mode of action of pyrazolopyran(+)-85 and pyrazolopyran(+)-86 with the most attractive inhibition efficiency in Plasmodium falciparum and P. vivax SHMTs (in the Schiff base form of PLP-L-serine (PLS) bound enzyme). The binding free energy results indicated the binding affinity of pyrazolopyran(+)-86 to Plasmodium SHMTs that is more favorable than pyrazolopyran(+)-85 by ∼ 2 kcal⋅mol−1, supported by the stronger ligand–protein hydrogen bonding and the lower solvent accessibility within the enzyme active site. According to the per-residue decomposition free energy analysis, residues L124, G128, H129, L130, K139, N356, and T357 are essential for inhibitors binding. By the rational structure-based drug design, the isopropyl moiety on the pyrazolopyran core should be changed to the negatively charged group (e.g., carboxylate group) for interacting with the positively charged residue R371. Alternatively, the phenolic compounds could be substituted with a phenyl or piperidine ring to promote hydrogen bond formation with the surrounding residues. Therefore, our findings presented here provide insights into the mode of inhibition of pyrazolopyran-based inhibitors and rational ideas for designing novel antimalarial drugs targeting Plasmodium SHMTs.